Teaching "Spanishness": nationalist ideology in texts for children in post-war Spain - Todd, Daniel (Kansas State University, 2014)
Early in the twentieth century, children’s literature in Spain developed greatly in terms of quality and distribution thanks in large part to the appearance of new publishing houses, illustrators and authors. Additionally, increased demand brought with it new translations of many foreign texts for children. Despite these early developments, children’s literature suffered a dramatic change after the establishment of Francisco Franco’s Nationalist regime; during the post-war period many types of literature were heavily censored, while children’s literature in particular devolved into what was in large part an ideological tool. Many of the texts for children during this period either directly or indirectly propagated a conception of “Spanishness” that excluded non-Catholics, particularly Iberian Muslims and those that supported the Second Spanish Republic that the Nationalists had toppled. Much like the Reconquista fought against the Iberian Muslims centuries earlier, the Spanish Civil War was often represented as a sort of crusade against non-Catholic (and therefore “non-Spanish”) Others. Many texts for children presented the elements of this narrative by means of auto-images (images of the Nationalist conception of “Spanishness”) and hetero-images (typically images of the “Otherly” Republicans and Muslims). The contrasts formed between these two sorts of images reveal how Spanish children were taught to conceive of themselves, as well as the Others of the Nationalist narrative. The texts discussed in this report include two civics texts (Así quiero ser: El niño del nuevo estado [1943] and España nuestra: El libro de las juventudes españoles [1943]), as well as two comic books (El Guerrero del Antifaz [1943-1966] and Flechas y Pelayos [1938-1949]) that were chosen for their representativeness of the sorts of texts widely available to and read by children during the post-war period.
Keywords: Literature; Literature (0401)